2006
DOI: 10.1007/s11538-005-9033-0
|View full text |Cite
|
Sign up to set email alerts
|

How Salmonella typhimurium measures the length of flagellar filaments

Abstract: We present a mathematical model for the growth and length regulation of the filament of the flagellar motor of Salmonella Typhimurium. Under the assumption that the molecular constituents are translocated into the nascent filament by an ATP-ase and then move by molecular diffusion to the growing end, we find a monotonically decreasing relationship between speed and velocity of growth that is inversely proportional to length for large length. This give qualitative but not quantitative agreement with data of th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Derivation of this formula is based on an injection-diffusion model where flagellin monomers, which are at least partially α-helical inside the channel (Shibata et al, 2007), are pushed by a pmf-driven export apparatus into the channel and move diffusively in one dimension through the length of the flagellum (Stern and Berg, 2013; Keener, 2006). An analytical expression for the flagellum length dependent growth rate is based on a continuum injection-diffusion model for the growth of flagellar filaments.…”
Section: Resultsmentioning
confidence: 99%
“…Derivation of this formula is based on an injection-diffusion model where flagellin monomers, which are at least partially α-helical inside the channel (Shibata et al, 2007), are pushed by a pmf-driven export apparatus into the channel and move diffusively in one dimension through the length of the flagellum (Stern and Berg, 2013; Keener, 2006). An analytical expression for the flagellum length dependent growth rate is based on a continuum injection-diffusion model for the growth of flagellar filaments.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, both Western blots and structural analyses indicate that CsrA Bb specifically impacts PF synthesis by regulating FlaB synthesis and filament length. In the enteric bacteria, the regulation of flagellar filament length is proposed to be measured based on the rate of the secretion of FlgM (Keener, 2006). During the early synthesis of flagellar filament, the secretion of FlgM through the completed basal body‐hook complex is rapid.…”
Section: Discussionmentioning
confidence: 99%
“…The latter depends on the diffusion of actin monomers to the tip, which results in a length-dependent rate of assembly. It has also been suggested that a diffusion-induced length dependence of the assembly rate plays a role in the control of the hook length in bacterial flagella (11). A different balance mechanism appears to control the length of microtubules in yeast, where kinesin motors move processively to the microtubule tips where they catalyze disassembly.…”
Section: Introductionmentioning
confidence: 99%